Kualitas Perkawinan Individu Yang Menikah Tanpa Pacaran (Courtship Model) - Al Husna; Hepi Wahyuningsih (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2007)
This research airned to compare quality of marriage between subjects who decided to engage in marriage without matching factor. Qualitative method was applied in this research. Five subjects were involve, having criteria such as : 1) married without dating process, 2) married not based on matching factor, 3) this is their first marriage and 4) already having child (ren).Based on research findings it is concluded that religiousty is the basic reason for them in deciding to get married. The quality of their marriage is influenced by adjustment along marriage, husband/wife (couple) evaluation to each other and role distribution. Role distribution is considered as potential source for marriage conflict. Marriage conflict should overcome through communication and social support. It is surprisingly found that marriage conflicts which were well handle and cohesivity were able to strengthen marriage quality. Keywords : marriage quality, dating, couple evaluation